"I Could Not Believe That Would Happen": Challenges and Opportunities in a Critical, Project-Based Clinical Experience. Issue 3 (3rd July 2018) - Burke, Kevin J.; Harman, Ruth; Hadley, Heidi Lyn; Mizell, Jason D.
ABSTRACT: As part of a youth summer program—a partnership between a large Southeastern university and the local school district—middle-school-aged youth, preservice teachers, and doctoral candidates interested in arts-based literacy practices spent their mornings in June 2016 engaging in activities that both explored and expanded thinking around their communities, schools, and families. Whereas the youth were enrolled in a monthlong creative arts and tentative unschooling experiment that ran roughly the length of a typical school day, university faculty and graduate students were engaged in a course on the application of youth participatory action research (YPAR). This article is an examination of the experience of preservice teachers, through an analysis of their reflections on events within the course, to suggest ways forward through the promises and perils of project-based, clinical preservice teaching experiences. In our exploration of the experiences of focal preservice teachers when engaged with youth coresearchers in a monthlong YPAR project, we found the work to have been filled with contradictions, unexpected shifts, and moments of great understanding, community affiliation, and suffering.